Genetic responses of some economic traits for selection of Surti buffalo - TAILOR, S P; BANERJEE, A K (The Indian Journal of Animal Sciences, 2013)
First lactation records of 507 Surti buffaloes, sired by 41 bulls, maintained at the Net-work Project on Buffaloes, ,Livestock Research Station, Vallabhnagar (1977-92) were utilized to-estimate direct and correlated responses. The genetic gain through mass selection was higher in FSP at 4.02% YPY at 10.0% and MY/FLL at 5.40% of their phenotypic averages, respectively, among reproduction, production and efficiency traits. The indirect selection based on lower AFC on and AFC would increase FSP, FDP and' decrease in the production. (FPY, YPY, 305FLMY, FLMY and LTP) and eiliciency traits (MY/FLL, MY/FCI and MY/ASC) which is in undesirable direction. In general, the emphasis on selection for improving reproductive efficiency lead to decline in production performance indicating the presence of production reproduction antagonism. The selection for higher first lactation peak yield would lead to an increase of 14.257, 46.929, 50.306, 0.150 , 0.099,0.015 and 111.943 kg per generdtion in YPY. 305FLMY, FLMY, MY/FLL, MY/FCI, MY/ASC and LTP respectively. However, it will also increase AF Con AFC, FSP and FCl. Therefore, selection on the basis of FPY will save the time, which is required to have complete record. This will also reduce the generation interval thereby increasing genetic gain per unit time.